The Influence of Leadership Style, Work Environment, and Work Conflict on Employee Work Productivity at Perum Perhutani Central Java Regional Division - Dina Melany; Amron Amron; Yohan Wismantoro; Roymon Panjaitan; Muhammad Azam (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research was conducted to determine the extent to which leadership style, the work environment, and work conflict influence employee work productivity at Perum Perhutani, Central Java Regional Division. A quantitative approach using a survey method was applied, in which questionnaires were distributed to 80 permanent employees. The collected data were measured using a Likert scale and processed with IBM SPSS Statistics. The findings show that leadership style positively and significantly contributes to employee work productivity, while the work environment serves as the most influential factor in enhancing productivity. In contrast, work conflict has a negative and significant impact, despite the relatively low conflict level within the organization. The study found that the work environment has the strongest influence on employee productivity, followed by leadership style, while work conflict has the least impact. Overall, the results highlight that fostering a supportive work environment, ensuring effective leadership, and minimizing conflict are essential for maintaining consistent employee work productivity.